(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Amaranth stands out as a focal point of interest among agricultural practitioners and researchers owing to its remarkable attributes. Renowned for its rich protein content, robust productivity, and diverse nutritional profile, amaranth emerges as a versatile resource with multifaceted applications. Beyond its conventional roles in food and fodder production, its stature as a medicinal plant of unparalleled worth further accentuates its significance. This review explores the utilization of various components of the amaranth plant, including its stem, leaves, and grain husk, as invaluable fodder sources in livestock farming. Notably, the infusion of amaranth into silage, particularly in conjunction with corn, emerges as a pivotal strategy for addressing year-round fodder requirements. The amalgamation of corn’s high sugar content with amaranth’s protein richness yields silage of heightened nutritive value, fostering accelerated growth and enhanced health parameters in livestock. By shedding light on the myriad benefits and potential applications of amaranth across agricultural and medicinal domains, this review aims to underscore its pivotal role in sustainable farming practices and human well-being.